HUBUNGAN SIFAT-SIFAT KEPEMIMPINAN DAN PENGETAHUAN KOMUNIKASI DENGAN KINERJA KEPALA SD DI BANDAR LAMPUNG - Mashar, Ali (STKIP Al Islam Tunas Bangsa Bandar Lampung, 2019)
The purpose of this research was to explain the correlation between the leadership traits and the communication knowledge with the headmasters’performance of SD in Bandar Lampung. This research has three hypotheses. First, there is a correlation between the leadership traits with the headmasters’performance. Second, there is a correlation between the communication knowledge with the headmasters’performance of SD in Bandar Lampung. Finally, there is a correlation between the leadership traits and the communication knowledge with the headmasters’ performance of SD in Bandar Lampung. The population of this research was all the headmasters of SD in Bandar Lampung, 106 in number, of which 53 were selected as a sample by means of the stratified proportional random sampling technique. Data were collected by using the Likert’s scale model in a questionnaire and analysis by means of the Alpha Cronbach analysis technique and an achievement test by using the Kruder Richardson (KR.20) analysis. The Data were analyzed by using the correlation and regression techniques. It was found that ry1 = 0.451 and r2y2 = 0.203401, ry2 = 0.308 and r2y2 = 0.094864. It means that the leadership traits and the communication knowledge contribute to the headmasters’performance is 20.34 % and 9.49 % respectively. Meanwhile it was also found that both the leadership traits and the communication knowledge contributed simultaneously 26.11 % to the headmasters’performance. It can be concluded that three hypotheses were supported by the data.